2021
DOI: 10.1016/j.jpha.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A dual-signal sensor for the analysis of parathion-methyl using silver nanoparticles modified with graphitic carbon nitride

Abstract: A highly sensitive and selective method was developed for both UV–vis spectrophotometric and fluorimetric determination of organophosphorus pesticides (OPs). This method used silver nanoparticles (AgNPs) modified with graphitic carbon nitride (g-C 3 N 4 ). The AgNPs reduced the fluorescence intensity of g-C 3 N 4 . Acetylthiocholine (ATCh) could be catalytically hydrolyzed by acetylcholinesterase (AChE) to form thiochol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Recently, they attracted great attention as optical probes for several organic pollutants because of their strong absorption band, which is very sensitive to the particle size, shape, and relative permittivity of the local environment, in the visible region of light 53 . AgNP-based optical sensors were reported for the detection of pesticides 20,[54][55][56][57][58][59] , organic dyes 60 , drugs [61][62] , nitro-aromatics 63 , and mycotoxins 64 . Electrochemical sensors, such as AgNP-based electrochemical sensors, are considered promising for detecting organic pollutants with sufficient sensitivity and selectivity compared with the optical sensors 65 .…”
Section: Agnps For Detecting Organic Pollutantsmentioning
confidence: 99%
“…Recently, they attracted great attention as optical probes for several organic pollutants because of their strong absorption band, which is very sensitive to the particle size, shape, and relative permittivity of the local environment, in the visible region of light 53 . AgNP-based optical sensors were reported for the detection of pesticides 20,[54][55][56][57][58][59] , organic dyes 60 , drugs [61][62] , nitro-aromatics 63 , and mycotoxins 64 . Electrochemical sensors, such as AgNP-based electrochemical sensors, are considered promising for detecting organic pollutants with sufficient sensitivity and selectivity compared with the optical sensors 65 .…”
Section: Agnps For Detecting Organic Pollutantsmentioning
confidence: 99%
“…22 Recently, electrochemical biosensors [23][24][25][26][27][28] and dual signal sensors using fluorometric and colorimetric read-outs have been developed, based on noble metal nanomaterials like gold and silver nanoparticles. [29][30][31][32] Limitations, in this case, include interfering electroactive materials and additional electrode modification required to get reliable outcomes. 33,34 Using nanomaterials as analytical probes nevertheless has many advantages because of their simple preparation and treatment, relatively low cost of required reagents, as well as rapid, selective, and sensitive results.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, electrochemical biosensors 23–28 and dual signal sensors using fluorometric and colorimetric read-outs have been developed, based on noble metal nanomaterials like gold and silver nanoparticles. 29–32 Limitations, in this case, include interfering electroactive materials and additional electrode modification required to get reliable outcomes. 33,34…”
Section: Introductionmentioning
confidence: 99%
“…Silver with the highest electrical conductivity among metals possess various outstanding properties suitable for electrochemical sensor development, such as a large surface-to-volume ratio, facilitates electron transfer, non-toxicity, and biocompatibility [ 27 ]. Moreover, various research have reported the excellent electrocatalytic activity of silver nanoparticles [ 28 , 29 , 30 ]. Hence, CuO was doped with Ag nanoparticles in this work.…”
Section: Introductionmentioning
confidence: 99%